The prognostic model based on tumor-associated neutrophils contributes to the stromal landscape and influences metabolic reprogramming in colorectal cancer - Yin, Xinke; Jiang, Yuanling; Huang, Jinghua; Luo, Jiahuan; Xu, Liang; Yang, Qiong (Frontiers in Immunology, 2025)
BackgroundThe tumor microenvironment (TME) is highly complex and significantly influences cancer prognosis and drug sensitivity. Tumor-associated neutrophils (TANs) play a key role in the TME. In this study, we aimed to investigate the TANs-related markers in colorectal cancer (CRC) and develop an integrated signature for prognostic stratification.MethodsThe CRC single-cell RNA sequencing (scRNA-seq) data and RNA-seq data were obtained from TCGA and GEO. A risk score was calculated based on the 18 TAN-associated genes identified in CRC by scRNA-seq data and LASSO regression. Prognosis, stromal and immune infiltration landscape, metabolism, and treatment response were then investigated in the low- and high-risk score clusters using RNA-seq data.ResultsPatients with a High-risk score had a significantly worse survival outcome than those with a Low-risk score (p < 0.0001). The prognostic predictive potency of the risk score was validated in both the TCGA validation cohort (p < 0.0001) and the GEO cohort (p < 0.00015). The areas under the curves of 1-, 3-, and 5-year survival were 0.76, 0.74, and 0.70 in the TCGA training set; 0.78, 0.68, and 0.78 in the TCGA validation set; and 0.65, 0.64, and 0.62 in the GEO set. The risk score was related to T, N, and M stages. A prognostic nomogram was constructed, and the predictive accuracy was assessed by calibration curve analysis. Decision curve analysis showed the clinical utility of the nomogram. Furthermore, the High-risk score cluster was significantly associated with the levels of cancer-associated fibroblasts, as well as activity in the transforming growth factor-β and WNT pathway. In depth, the High-risk score cluster exhibited lower levels of amino acid, tricarboxylic acid, and nucleotide metabolism, as well as poorer responses to chemotherapeutic agents such as 5-fluorouracil.ConclusionThis novel TAN subtype, based on 18 prognostic-related genes, could provide new insights into the prognostic stratification and treatment options for CRC.